A cultural geography review on understanding the mechanisms of transformation in rural settlements: The case of İzmit district - Balci, Esra Ekesi; Sema Dincer, Iclal (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2024)
Rural areas, shaped by their internal dynamics, confront interconnected challenges such as an aging and sparse population, declining rural labor force, land division during inheritance transitions, and insufficient public services, including education, healthcare, commerce, and culture. Migration from rural to urban areas exacerbates pressures on rural areas, particularly heightened during crises such as epidemics, earthquakes, droughts, floods, regional conflicts, wars, and migrations with global repercussions. These challenges negatively impact communities and urban areas, increasing vulnerability to subsequent crises. The legislative framework for rural settlement planning in Turkiye is lacking, leading to the adoption of urban planning tools in rural contexts. However, rural areas, closely connected to nature, possess distinct knowledge. Unfortunately, this unique knowledge, akin to Bourdieu's habitus, is swiftly eroding. This study uniquely explores the analysis of rural areas through the lenses of habitus and cultural geography, combining two theoretical frameworks. The focus on Izmit as the sample field enhances its distinctive value in shedding light on these dynamics. This study delved into the impact of changing global dynamics on rural areas, particularly in Izmit. Uncontrolled transformations stemmed from central decisions, rural labor shifts, and urban migration, impacting culture, agriculture, and public spaces. To address these challenges, planning methodologies must adapt, incorporating on-site analyses and direct engagement with local inhabitants. Striking a balance between urban culture and rural sustainability is crucial. Efforts to understand the unique characteristics of a place, its inhabitants, and global trends are essential for fostering a harmonious transformation amidst the ongoing rapid changes in rural areas.
Keywords: Bourdieu's habitus; cultural; geography; Izmit rural; settlements; non-representational; theory; rural transformation.; Architecture